Women's Camera Work : Self/Body/Other in American Visual Culture - Davidov, Judith Fryer (Book collections on Project MUSE., 1998)
Women's Camera Work explores how photographs have been and are used to construct versions of history and examines how photographic representations of otherness often tell stories about the self. In the process, Judith Fryer Davidov focuses on the lives and work of a particular network of artists linked by time, interaction, influence, and friendship--one that included Gertrude Käsebier, Imogen Cunningham, Dorothea Lange, and Laura Gilpin. Women's Camera Work ranges from American women's photographic practices during the nineteenth and early twentieth centuries to a study of landscape photography. Using contemporary cultural studies discourse to critique influential male-centered historiography and the male-dominated art world, Davidov exhibits the work of these women; tells their absorbing stories; and discusses representations of North American Indians, African Americans, Asian Americans, and the migrant poor. Evaluating these photographers' distinct contributions to constructions of Americanness and otherness, she helps us to discover the power of reading images closely, and to learn to see through these women's eyes. In presenting one of the most important strands of American photography, this richly illustrated book will interest students of American visual culture, women's studies, and general readers alike.